Further Investigations on Antithrombin III in the Plasmas of Patients with the Abnormality of ‘Antithrombin III Budapest’ - Sas, Géza; Pepper, Duncan S; Cash, John D (Thrombosis and Haemostasis, 1975)
Antithrombin III (AT-III) was studied in a thrombophilic family with an abnormal AT-III molecule (antithrombin III Budapest) using a modified crossed Immunoelectrophoresis technique, gel filtration, ‘rocket’ Immunoelectrophoresis and a heparin cofactor assay.When plain agarose was applied in the first phase of the crossed Immunoelectrophoresis, the normal and the pathological AT-III revealed identical electrophoretic mobility. However, when heparin was mixed with agarose in the first phase of electrophoresis, the propositus’ plasma displayed a different AT-III pattern from normal plasma. His plasma contained the first component of the normal plasma (Immune Antithrombin III1, IAT-III1) in a concentration of only 5% of normal, and a protein in high concentration which although immunoreactive to AT-III antisera, had an electrophoretic mobility similar (but not identical) to that of IAT-III2. This ab-normal protein had no heparin cofactor activity and a molecular size greater than normal plasma AT-III. Unlike normal AT-III, the addition of heparin did not change the molecular size of the pathologic AT-III molecule significantly.The abnormal protein was present in lower concentrations in the patient’s children and at the time of study they had no clinical or laboratory evidence of intravascular coagulation.